2016
DOI: 10.1039/c6ra09695f
|View full text |Cite
|
Sign up to set email alerts
|

A novel low-temperature solid-state route for nanostructured cubic garnet Li7La3Zr2O12 and its application to Li-ion battery

Abstract: We present a novel approach to the solid-state synthesis of garnet-type cubic Li7La3Zr2O12 (c-LLZO) nanostructured particles with 1.0 mass% Al at 750 o C within 3 h. In contrast to conventional solid-state processes, a highly reactive precursor was prepared in two steps: (i) by homogenizing the stoichiometric mixture without Li, and (ii) subsequent addition of Li in the form of an ethanolic solution of lithium acetate. The actual composition determined by ICP analysis was Li6.61La3Zr2Al0.13O11.98. Sintering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Both higher and lower conductivities have been reported in the literature; they range from 0.001 mS cm -1 , 23 to 0.16 mS cm -1 , 24 to 0.99 mS cm -1 . The principal sophistication in flash is programming of the power supply which provided electrical voltage and current to the specimen.…”
Section: θ (°)mentioning
confidence: 90%
“…Both higher and lower conductivities have been reported in the literature; they range from 0.001 mS cm -1 , 23 to 0.16 mS cm -1 , 24 to 0.99 mS cm -1 . The principal sophistication in flash is programming of the power supply which provided electrical voltage and current to the specimen.…”
Section: θ (°)mentioning
confidence: 90%
“…The bands between 100 and 150 cm −1 were the vibrations of La cations where the wide band at about 640 cm −1 could be ascribed as Zr―O bond stretching. It has been recently reported that the Raman shift at 157 cm −1 was the characteristic peak of the tetragonal LLZO phase, and the shift at 289 cm −1 was continually decreased and disappeared when cubic LLZO phase was stabilized . The band at around 520 cm −1 was T 2g mode of Li 2 O and appeared first in the sample sintered at 1100°C …”
Section: Resultsmentioning
confidence: 88%
“…It has been recently reported that the Raman shift at 157 cm −1 was the characteristic peak of the tetragonal LLZO phase, and the shift at 289 cm −1 FIGURE 2 XRD patterns of wet and dry mixed precursors for solid-state LLZO synthesis was continually decreased and disappeared when cubic LLZO phase was stabilized. 16,17 The band at around 520 cm −1 was T 2g mode of Li 2 O and appeared first in the sample sintered at 1100°C. 18 The presence of Li 2 O in Figures 3 and 4 was believed to be due to the well-documented Li exclusion phenomenon during Al incorporation in cubic LLZO structure based on the reaction given below: 19 Li…”
Section: Thermodynamic Calculationsmentioning
confidence: 96%
“…However, the solid‐solid contact of the electrolyte/electrode leads to a large Li + transmission resistance at the interface . Moreover, Li + ions also exhibit poor transport performance inside the solid electrode without a liquid electrolyte, which is not beneficial for the reaction of the electrode materials (low capacity) and fast charge/discharge (low rate performance) . Reducing the interfacial resistance is crucial to the commercial application of ASSLBs …”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] Moreover, Li + ions also exhibit poor transport performance inside the solid electrode without a liquid electrolyte, which is not beneficial for the reaction of the electrode materials (low capacity) and fast charge/discharge (low rate performance). [37][38][39] Reducing the interfacial resistance is crucial to the commercial application of ASSLBs. [40] In this review, we mainly summarize the strategies used to reduce the interfacial resistance in ASSLBs based on OCEs.…”
Section: Introductionmentioning
confidence: 99%